Perlindungan Hukum Terhadap Anak Dibawah Umur (Balita) Dalam Mengkonsumsi Makanan Ringan Kadaluarsa (Expired) - Milawartati, Milawartati (Universitas Batanghari Jambi, 2024)
The number of snack products circulating in the market will make children (toddlers) as consumers in terms of making a decision to buy a product is very much different from adults, and children as consumers who will become victims of business actors who are not in good faith, by selling expired snacks in order to reap profits. This can have a negative impact on the health of children (toddlers) and can even be life threatening. Therefore, the problem that will be examined in this research is how is the legal protection of children under five in consuming expired snacks? and how is the form of responsibility of business actors who deliberately sell expired snacks? The purpose of this research is to find out the legal protection of children under five in consuming expired snacks, and to find out the form of responsibility of business actors who deliberately sell expired snacks. This research method uses normative legal research methods or doctrinal research. Examining the basis of rules and regulations regarding consumer protection efforts against minors (toddlers) in consuming expired snacks both horizontally and vertically sourced from Primary Legal Materials, Secondary Legal Materials, and Tertiary Legal Materials. Conclusion: legal protection of consumers (children under five) can be done preventively and refresively, and the responsibility of business actors in criminal, civil and administrative matters as contained in the GCPL Law.